2008
DOI: 10.1086/590430
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis during an Outbreak of Acute Hepatitis C Virus Infection in HIV‐Infected Men: A Prospective Cohort Study

Abstract: Outbreaks of acute hepatitis C virus (HCV) infection are occurring in HIV-infected men who have sex with men. We evaluated risk factors and liver histopathology in 11 consecutively enrolled men with newly acquired HCV infection that was diagnosed on the basis of antibody seroconversion, new elevations in alanine aminotransferase level, and wide fluctuations in HCV RNA level. Ten patients reported unprotected anal intercourse, and 7 reported “club-drug” use, including methamphetamine. Liver biopsy showed modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 15 publications
3
67
0
3
Order By: Relevance
“…Initial observational data from HIV-uninfected patients with acute HCV infection showed a remarkably high rate (98%) of sustained virological response in 44 individuals [232].…”
Section: Managementmentioning
confidence: 99%
“…Initial observational data from HIV-uninfected patients with acute HCV infection showed a remarkably high rate (98%) of sustained virological response in 44 individuals [232].…”
Section: Managementmentioning
confidence: 99%
“…States [28] and Australia [29], HCV has unexpectedly emerged as an STI among HIV-positive MSM. Longitudinal cohort studies have confirmed a marked increase in HCV incidence among HIVpositive MSM, but not HIV-negative MSM, after the year 2000.…”
Section: As Well As In the Unitedmentioning
confidence: 99%
“…HIV/HCV co-infection negatively influences the natural course of HCV infection, in particular when HCV is acquired after HIV and at an older age (>40 years) [28]. HIV/ HCV co-infection is associated with lower rates of spontaneous viral clearance, accelerated progression to liver disease and less favourable treatment outcome [38].…”
Section: As Well As In the Unitedmentioning
confidence: 99%
“…Furthermore, outbreaks of sexually transmitted HCV infections have been reported among HIV-infected MSM in several European countries (3,7,13,16,36,44), Australia (27), and North America (9,24,37). Phylogenetic analysis also revealed monophyletic transmission clusters of HCV within the MSM populations of major cities in England, France, The Netherlands, and Germany; this HCV incidence had already increased among HIV-infected MSM from the mid-1990s (44,46).…”
mentioning
confidence: 96%